Bioiogical control of Pseudomonas avenae with epiphytic bacteria isolated from corn. II Selection and evaluation of antagonists. - Lopes, Carlos Alberto; Stall, Robert E. (Pesquisa Agropecuaria Brasileira, 2014)
Of 179 bacteria collected from corn plants in three locations, 34 were antagonistic in vitro to Pseudomonas avenae. Among these, 29 were fluorescent pseudomonads. Various levels of control of bacterial leaf blight and stalk rot (BLBSR) on sweet corn were obtained, but no relationship was found between antagonism in vitro and disease control. In greenhouse, strains E-11 and E-24 of P.fluorescens and strain U-46 of Bacillus sp. Consistently controlled BLBSR on sweet corn. Control achieved with E-11 was equivalent to reducing the inoculum dose (ED 50) of P. avenae by at least 1000 times, as determined by infectivity titrations. In the field, E-11 controlled BLBSR as effectively as 100 ppm streptomycin when treatments were applied immediately before inoculation with P. avenae. Streptomycin applied 12 or 24 hr before inoculation did not control the disease, whereas E-11 reduced BLBSR severity by more than 50%. Antagonist U-46 did not affect disease development at any time of application. Antagonist F-11 was recovered from corn whorls for eight days after application to plants, but U-46 was not recovered 84 hr after application